"Niveles de inclusión de Morera (Morus alba) en el engorde de cuyes séxados (Cavia Porcellus Linnaeus)". - Quiñonez González, Cecilia Liliana (2020)
The research was carried out at the "La María" Experimental Campus of the Quevedo State Technical University (UTEQ), located at km. 7 ½ of the Quevedo-El Empalme road, Mocache Canton, Los Ríos Province, whose geographical location is 1 ° 3'18 ”south latitude and 79 ° 25 '24' 'west longitude, at a height of 77.60 masl , with a duration of six weeks. The objectives being: To determine the productive behavior of sexed guinea pigs (Cavia porcellus Linnaeus), fed with different levels of inclusion (0; 10; 20; 30 and 40%) of mulberry flour (Morus alba) in the diet) and determine the profitability of treatments. A factorial arrangement 2 (sex) x 4 (levels of inclusion) was applied, within a Completely randomized Block Design (DBCA), with four repetitions. To determine the differences between treatment means, the Tukey test (P≤0.05). 40 guinea pigs (20 males and 20 females) 35 days old, with an average weight of 326.6 g, were used. Feed intake (g), weight gain (g), feed conversion rate, carcass weight (g), carcass yield (%) and profitability (%) were evaluated. Sex (males-females) did not affect the guinea pigs' productive response (P˃0.05). The inclusion levels (0; 10; 20; 30 and 40%) of mulberry meal in the diet did not increase (P˃0.05) the final weight (620.38; 615.63; 631.50; 673.00 and 653.25 g), the gain of weight (7.39; 7.47; 7.74; 9.07 and 7.62 g animal-1 day-1), feed consumption (25.85; 26.53; 26.13; 28.57 and 26.88 g animal-1 day-1), feed conversion index (3.70 ; 3.84; 3.42; 3.31 and 3.80). However, the 30% inclusion level recorded the highest (P˂0.05) carcass weight (481.00 g), carcass yield (71.61%); and the highest profitability in males and females fed with 30% inclusion of mulberry in the diet (45.84 and 42.14 %, respectively). The inclusion of mulberry flour in diets for fattening guinea pigs allows reaching commercial weights of 638.74 g at 70 days of age, considering it as an alternative diet for this species in the area of influence of the Quevedo State Technical University (UTEQ). Key words: nutrition, feeding, forages, diets, guinea pigs.